Intracellular synthesis of gold nanoparticles using alga tetraselmis kochinensis - Senapati, Satyajyoti; Syed, Asad; Moeez, Sana; Kumar, Ashutosh; Ahmad, Absar (Materials Letters, 2012)
The development of eco-friendly synthesis protocol for the synthesis of nanoscale materials of different compositions, shapes and sizes is an important area of research in the field of nanotechnology. In this paper, we report on the use of alga Tetraselmis kochinensis in the intracellular synthesis of gold nanoparticles of dimensions 5-35 nm. The particles are more concentrated upon the cell wall than on the cytoplasmic membrane, possibly due to reduction of the metal ions by enzymes present in the cell wall and cytoplasmic membrane. These intracellular nanoparticles may have applications in drug delivery, biomedical applications, catalysis, etc. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Algae; Biosynthesis; Nanoparticles; nanotechnology; Tetraselmis kochinensis